Ferrofluids for heat transfer enhancement under an external magnetic field. (August 2018) - Gan Jia Gui, N.; Stanley, C.; Nguyen, N.-T.; Rosengarten, G.
Highlights: Ferrofluids have higher thermal conductivity than their base fluids. Magnetic nature of ferrofluid allow manipulation of flow via external magnetic flux. Heat transfer properties of the flow are enhanced using ferrofluidic plug flow. Higher solid volume concentration of magnetic particles enhance heat transfer rate. Increasing magnetic flux decreases heat transfer enhancement. Abstract: Overheating of power electronic devices has become a significant issue due to their continued miniaturization and increased heat flux that needs to be dissipated. Ferrofluids (magnetic nanofluids) have been shown to have higher thermal conductivity than their base aqueous or oil based fluids due to the solid magnetic nanoparticles that make up the ferrofluid. This allows higher convective heat transfer rates and, importantly, the ability to externally effect the flow using a magnetic field. In this paper, we focus on material characterization of ferrofluids and measurement of heat transfer rates for single-phase ferrofluidic forced convective flow in microchannels. We show that heat transfer properties of the flow are enhanced with the use of ferrofluids and that the material make-up of the ferrofluid affects these properties. In this paper, we argue that generally, convective heat transfer rates for ferrofluids are increased by increasing the solid volume concentration of magnetic particles (∼0.2–0.4%). Interestingly, increasing magnetic flux was shown to decrease heat transfer enhancement. This was due to a reduction in the thermal conductivity of the bulk fluid caused by magnetic nanoparticles being drawn out of the isotropic mixture and becoming pinned to the channel wall in the region of strongest magnetic field. We show that there is good correlation between both theory and experimental visualization of this phenomenon.